(untitled) (CIPEEX, 2024)
THE DECREASE IN IMMUNIZATION DEMAND IS A SIGNIFICANT PUBLIC HEALTH ISSUE, SINCE SEVERAL DISEASES THAT HAVE ALREADY BEEN CONTROLLED CAN ONCE AGAIN CIRCULATE IN THE COUNTRY. IT IS WORTH HIGHLIGHTING THAT ONE OF THE MAIN CAUSES OF THIS MISFORTUNE IS THE INFODEMIC, A TERM USED TO REFER TO THE UNCONTROLLED DISSEMINATION OF INFORMATION. THIS APPROACH SEEKS TO DEMONSTRATE THE CONSEQUENCES THAT THE INFODEMIC HAS HAD ON THE BRAZILIAN POPULATION IN TERMS OF VACCINATION COVERAGE AND EPIDEMIOLOGICAL CONTROL OF DISEASES, AS WELL AS PRESENTING POLICIES AND ACTIONS APPLIED IN ORDER TO MITIGATE THE IMPACTS ON A NATIONAL SCALE. THIS QUALITATIVE INTEGRATIVE REVIEW ANALYZED STUDIES WITH UNIQUE METHODOLOGICAL APPROACHES. THE ANALYSIS WAS CARRIED OUT IN THE MEDLINE, VHL, SCIELO, CAPES, PUBMED, LILACS AND VHL DATABASES. THREE INCLUSION CRITERIA WERE USED (A) ARTICLES ON PUBLIC HEALTH IN THE FIELD OF IMMUNIZATION; (B) NATIONAL (PORTUGUESE) AND INTERNATIONAL (ENGLISH) PUBLICATIONS; (C) ARTICLES PUBLISHED BETWEEN 2018 AND 2023. TO VALIDATE THE CRITERIA, THE FOLLOWING STAGES WERE ANALYZED: TITLE, ABSTRACT, KEYWORDS AND INTRODUCTION OF THE ARTICLES. EXCLUSION CRITERIA WERE THEN APPLIED: (A) ARTICLES NOT FOUND IN THEIR ENTIRETY; (B) ARTICLES USING A METHODOLOGY THAT DOES NOT FIT INTO THE CONTEXT OF IMMUNIZATION; (C) STUDIES THAT DO NOT FIT INTO THE FIELD RESEARCH, CASE STUDY, INTEGRATIVE AND SYSTEMATIC REVIEW MODALITY, WITH THE CENTRAL THEME OF "INFODEMIA"; (D) DUPLICATE ARTICLES AND RESEARCH THAT DOES NOT ADDRESS RESULTS IN HEALTHCARE PROCESSES, WITH A FOCUS ON CONTINUOUS IMPROVEMENT AND WASTE REDUCTION. TO CARRY OUT THE DESCRIPTIVE STATISTICAL ANALYSIS, THE DATA WAS ENTERED INTO TABLES IN THE MICROSOFT OFFICE EXCEL 2010 FOR WINDOWS PROGRAM, WHERE THE VARIABLES WERE PRESENTED IN THEIR ABSOLUTE AND RELATIVE VALUES. HOWEVER, THE FOLLOWING RESULTS WERE OBTAINED: TOTAL NUMBER OF ARTICLES= 278728,442; BETWEEN THE YEARS 2018-2023= 152157; LANGUAGES PORTUGUESE AND ENGLISH= 26147; TITLES READ= 50; ABSTRACTS READ= 50; READ IN FULL=19. A TABLE SHOWS THE 19 ARTICLES SELECTED AND ANALYZED, ACCORDING TO THE CRITERIA INDICATED IN THE METHODOLOGY OF THIS STUDY. THUS, ASSERTIVE COMMUNICATION DEMONSTRATING THE EFFICACY AND SAFETY OF THE VACCINE WAS FOUND TO BE PRESENT, BUT THERE ARE STILL GAPS THAT LEAVE THE POPULATION UNINFORMED, WHICH IS WHY IT IS IMPORTANT TO CONDUCT A BEHAVIORAL INVESTIGATION OF THE POPULATION IN ORDER TO CONVEY A POSITIVE VIEW, FOR POSSIBLE CLARIFICATION ON THE EFFICACY AND SAFETY OF THE VACCINE. HOWEVER, IF THIS IS DONE, IT COULD LEAD TO AN INCREASE IN VACCINATION COVERAGE, PREVENTING A POSSIBLE RESURGENCE OF VACCINE-PREVENTABLE DISEASES.